(untitled) (Eurasian Scientific Herald, 2023)
Innovative approaches to assessment can help learners to demonstrate skills for society, employment and education. Mobile technology means that many learners now have direct access to handheld computing. As a result, different types of assessment can now be produced and applied. You’ll move on to investigate what skills are needed by learners in today’s society and how innovative approaches to assessment might help educators to help learners demonstrate these skills. You’ll also look at how innovative assessments can be used to more closely reflect what is taught and how learning can be more closely aligned to the skills required for employment and access to higher education.